Non-anatomical Anterior Cruciate Ligament Remnants Do Not Contribute Dynamic Knee Stability ˜Quantitative Measurement Of The Pivot Shift Test˜ - Nagai, Kanto (Orthop J Sports Med, 2014)
OBJECTIVES: In anterior cruciate ligament (ACL) injured patients, thick ACL remnants were frequently observed and bridged between the tibia and either femur or posterior cruciate ligament (PCL) at the arthroscopic inspection. There were several reports regarding the biomechanical function of ACL remnants, however, its biomechanical function has not been fully examined. Therefore, the purpose of this study is to quantitatively evaluate the biomechanical function of ACL remnants in antero-posterior (A-P) and dynamic knee stability in ACL injured patients. It is hypothesized that the ACL remnants, which are attached to the non-anatomical ACL insertion sites, did not contribute to the knee stability. METHODS: 121 unilateral ACL injury patients who underwent primary ACL reconstruction were examined. Partial ACL tears, in which intact anteromedial or posterolateral bundles were observed, were excluded. The patients who had severe collateral ligament injury, PCL injury or contralateral knee injury were also excluded. All patients were evaluated under general anesthesia before ACL reconstruction. Anterior tibial translation (ATT) was measured using the KT-1000 Knee Ligament Arthrometer with the knee at 30 degrees of flexion in both injured and contralateral knee, and the mean side-to-side difference in ATT was calculated. ATT during the Lachman test, and tibial acceleration during the pivot shift test were also measured with electromagnetic measurement system as we previously reported. The mean side-to-side difference in ATT during the Lachman test was also calculated. Subsequently, arthroscopic evaluation was performed, and the ACL remnants were classified into 4 morphologic patterns as follows, group 1: bridging between PCL and tibia, group2: bridging between the roof of intercondylar notch and tibia, group3: bridging between the lateral wall of the intercondylar notch and tibia, group 4: no substantial ACL remnants. All values were showed as mean ± standard deviation. One way Analysis of variance (ANOVA) was used to compare each value between 4 groups, and post hoc analysis was performed using Fisher’s protected least significance difference test. A P-value <0.05 was considered statistically significant. RESULTS: The patterns of ACL remnants were as follows, group1: 27 knees, group 2: 34 knees, group 3: 27 knees, group 4: 33 knees (Table 1). The mean side-to-side difference of ATT using KT-1000 arthromerter was 5.2±3.4, 5.7±3.1, 3.4±2.0, 5.9±3.0 (mm) in group 1, 2, 3, and 4 respectively. In group 3, the mean side-to-side difference of ATT using KT-1000 arthrometer was significantly smaller than those in group 2, 4 (p<0.05). That in group 1 was larger than that in group 3, but there was not statistically significant difference. The mean side-to-side difference of ATT during the Lachman test in group 3 was significantly small compared with those in group 1, 2 and 4 (p<0.05) (Figure 1A). On the other hand, there was no statistically significant difference in tibial acceleration between each group (Figure 1B). CONCLUSION: The main finding of this study was that ACL remnants of group 3 partially contributed A-P stability, whereas they did not contribute dynamic knee stability evaluated by tibial acceleration during the pivot shift test. These findings suggest that ACL remnants may not have enough contribution to the stabilization of the knee joint.